Influence of the level of speed-strength preparedness on the agility of volleyball players 12–13 years old - Шевченко, Олег; Паєвський, Володимир; Горчанюк, Юрій (Slobozhanskyi Herald of Science and Sport, 2018)
Oleg Shevchenko, Volodymyr Paievskyi & Yurii Horchanyuk Purpose: determine the impact level of indicators of speed-strength preparedness for the agility of young volleyball players 12–13 years. Material & Methods: analysis of scientific and methodological literature, pedagogical testing of speed-strength qualities and agility, pedagogical experiment, methods of mathematical statistics. The study involved 25 volleyball players aged 12–13 years, training in the basic training group of the second year of training of the sports club "Lokomotiv" in Kharkov. Young athletes were divided into an experimental – 13 people and a control –12 volleyball team. Results: after the introduction of the experimental methodology, a link was found between the level of speed-strength abilities and the agility of volleyball players. Conclusion: the positive influence of development of speed-strength qualities on indicators of agility of volleyball players that is necessary for selection of means and methods in training process of young athletes is proved.